elaah Konsepsi Pendidikan dan Implikasinya Bagi Terwujudnya Masyarakat Madani di Indonesia - Tutuk Ningsih (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Civil society concept is a new pursuit of Indonesian nation, especially after reformation era. Civil society formed through several ways and policy, one that relative effective is by education, with formal institute or at society. In spite of the fact that Education System act (UU Sisdiknas) is enough comprehensive to form holistic Indonesian people, thereâ€™s bias in its implication. This article is trying to trace different education theory, from several schools of thought, namely empiricism, nativism, naturalism, convergence, progressivism, essentialism, perennials, and constructivism. Those different thought affect education process, include its implication to build civil society. Teacher role, also school curriculum, leaning model, and tools and resources have critical role to reach desirable learning result.Â